2019
DOI: 10.3892/ol.2019.10429
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of carbonyl reductase 1 inhibits malignant behaviors and epithelial mesenchymal transition by suppressing TGF‑β signaling in uterine leiomyosarcoma cells

Abstract: Carbonyl reductase 1 (CBR1) has been reported to be involved in cancer progression. Recently, we found that CBR1 overexpression inhibited malignant behaviors and the epithelial mesenchymal transition (EMT) in uterine cervical cancer. It remained unclear whether this was also the case in uterine leiomyosarcoma (uLMS), which is derived from mesenchymal cells and is a much more malignant gynecological tumor. A number of previous studies suggested that malignant behaviors are associated with EMT, even in mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Gynecological malignancies account for 19% of new female cancer cases worldwide. There has been a steady increase in the incidence of gynecological malignancies, including cervical, endometrial, and ovarian cancers; in particular, the incidence of endometrial cancer has increased more than sixfold in 10 years [ 16 ]. Most patients with gynecological malignant tumors will have psychological problems before and after treatment, which will weaken the confidence of patients to overcome the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Gynecological malignancies account for 19% of new female cancer cases worldwide. There has been a steady increase in the incidence of gynecological malignancies, including cervical, endometrial, and ovarian cancers; in particular, the incidence of endometrial cancer has increased more than sixfold in 10 years [ 16 ]. Most patients with gynecological malignant tumors will have psychological problems before and after treatment, which will weaken the confidence of patients to overcome the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al reported that nicotine could inhibit matrix synthesis in the cartilaginous plate and reduce insulinlike growth factor expression resulting in delayed chondrogenesis, a decline in growth, and consequent weight loss at birth (7). The relationship between cytokines, such as transforming growth factor-beta (TGF-β1), and fibronectin expression have been previously reported, and the observed changes in fibronectin expression could be attributed to the effect of nicotine on these cytokines (15). TGF-β1, through downstream signals that belong to the protein family of Smads, initiates their activity by Smads2/3 phosphorylation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike tocopherol-α and rutin, AH, particularly AH1000, significantly downregulated SCC and UGF ( Figure 1 ). SCC binds to carbonyl reductase, which inhibits malignant behavior and TGF-β signaling in uterine cancer cells [ 25 ].…”
Section: Discussionmentioning
confidence: 99%